Perceptions of Stress Levels Among Mothers in Pasir Angin Village, Megamendung Subdistrict, Bogor, Based on the Perceived Stress Scale (PSS-10) - Dwi Nurmawaty; Erlina Puspitaloka Mahadewi; Ayu Larasati; Nina Sutinah (Sean Institute, 2025)
Stress is a negative reaction that arises when an individual experiences excessive pressure resulting from demands, difficulties, or situations that exceed their ability to cope. This study aims to describe the level of stress among women who serve as Posyandu cadres in Pasir Angin Village, Megamendung District, Bogor. This research uses a quantitative approach with univariate analysis. The population consists of all Posyandu cadres in Pasir Angin Village, totaling 31 individuals, and the entire population was used as the sample. Data collection was conducted using the Perceived Stress Scale (PSS-10). The results show that most Posyandu cadres experience moderate stress, with 23 respondents (74.2%), followed by mild stress experienced by 6 respondents (19.4%), and severe stress by 2 respondents (6.5%). These findings indicate that the majority of respondents experience stress at a moderate level, reflecting psychological pressure that is still manageable but requires attention to prevent progression to severe stress. Psychological support and capacity building through stress management training, more equitable task distribution, and routine monitoring of the cadres’ psychological